Vocabulary Learning Strategies Through Short Stories - Nayak, Tushar (UICELL, 2023)
The study envisages the use of short stories to enrich the vocabulary acquisition of elementary school students through the deployment of strategies with the help of dictionaries. The study aims to improve the vocabulary acquisition of elementary school students by suggesting suitable materials appropriate for their age, interest, and vicinity. Vocabulary learning strategies with the help of dictionaries have significantly influenced vocabulary acquisition in elementary school students. Thus, the study utilizes dictionary learning strategies from "Effective Language Teaching Practices" as a technique to be deployed while short stories reading to create awareness among the students about the new vocabulary and content encountered in reading. Therefore, the study suggests effective teaching methods to utilize dictionary learning strategies while reading short stories to improve the vocabulary learning of students. Keywords: Vocabulary, Short Stories, Language, Strategies, Dictionary